2009
DOI: 10.1002/nag.835
|View full text |Cite
|
Sign up to set email alerts
|

Flat boundaries and their effect on sand testing

Abstract: SUMMARYA study of the effect of the use of flat boundaries on the stressing of a sample of an idealized granular material with no applied shear is presented. Discrete element method (DEM) data of 1D compression were analysed and the local strain field inside the sample was investigated as the sample was stressed. A best-fit strain was seen to best describe the material behaviour free from boundary effects. The individual particle displacements were probed, providing insight into the behaviour of particles adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 15 publications
5
28
0
Order By: Relevance
“…Specimen height is less important here because no attempt is made to describe possible strain localisation inside the specimens. When localisation is of concern the strong horizontal boundary effects discussed by Marketos & Bolton (2010) should be considered.…”
Section: Upscaling Proceduresmentioning
confidence: 99%
“…Specimen height is less important here because no attempt is made to describe possible strain localisation inside the specimens. When localisation is of concern the strong horizontal boundary effects discussed by Marketos & Bolton (2010) should be considered.…”
Section: Upscaling Proceduresmentioning
confidence: 99%
“…The projected-area of this region was measured by connecting the centroids of the outer grains as shown for stages 1 and 4 in Figure 8 difference between major principal strains) calculated relative to the initial geometry in Figure 8(a) for the three subsequent deformation stages. The strains were calculated from the entire set of grain displacements using the best fit approach described in [41]. Positive volumetric strains indicate dilation.…”
Section: Macroscopic Response To Loadmentioning
confidence: 99%
“…Marketos and Bolton [10] showed how the apparent macroscale stiffness of an oedometric test could be strongly affected by the microscale details of the contact at the boundary top and bottom walls. For axisymmetric problems, Cui et al [6] and Arroyo et al [2] have shown that rigid walls enforcing symmetry conditions induce specific microstructural features and result in changes of macroscopic response.…”
Section: Introductionmentioning
confidence: 99%